2018
DOI: 10.1016/j.jmmm.2017.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Absorbing boundary layers for spin wave micromagnetics

Abstract: Micromagnetic simulations are used to investigate the effects of different absorbing boundary layers (ABLs) on spin waves (SWs) reflected from the edges of a magnetic nano-structure. We define the conditions that a suitable ABL must fulfill and compare the performance of abrupt, linear, polynomial and tan hyperbolic damping profiles in the ABL. We first consider normal incidence in a permalloy stripe and propose a transmission line model to quantify reflections and calculate the loss introduced into the stripe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…Magnetic parameters of permalloy are used in simulations: M s = 8 × 10 5 A/m and A = 13 pJ/m. In the dynamic simulations, a Gilbert damping constant of α = 0.001 is used to ensure a long-distance propagation of the spin-wave beams, and absorbing boundary conditions are adopted to avoid the spin-wave reflection by film edges [32]. An external field µ 0 H 0 = 1 T along +ŷ is applied to saturate the in-plane magnetization.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Magnetic parameters of permalloy are used in simulations: M s = 8 × 10 5 A/m and A = 13 pJ/m. In the dynamic simulations, a Gilbert damping constant of α = 0.001 is used to ensure a long-distance propagation of the spin-wave beams, and absorbing boundary conditions are adopted to avoid the spin-wave reflection by film edges [32]. An external field µ 0 H 0 = 1 T along +ŷ is applied to saturate the in-plane magnetization.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Finally, after a sufficiently long time τ , a 2D Fourier transform in space and time variables is performed in order to obtain the spin-wave spectrum. To avoid noise in the spectrum caused by the reflection of the spin waves at the sample edges, it has been shown that using a strong damping towards the sample edges minimizes this effect [146]. Alternatively, it is also possible to use periodic boundary conditions.…”
Section: Micromagnetic Simulations Of Spin Waves With Interfacial Dmimentioning
confidence: 99%
“…The damping parameter is reduced from α = 1 (used for static simulations) to a smaller value of 0.08 for NdCo x and 0.01 for Permalloy [36]. For Figure 8: (i) the surface of the working space was changed from squared (see above) to rectangular: 5.62 × 0.96 µm 2 ; (ii) the periodic boundary conditions were suppressed; (iii) an enveloping area with increased damping at the edges of the working area was used to simulate infinite extent samples (absorbing boundary conditions) [56]. The magnetic field was applied on a single row spin, transversal to the wavevector, → k in order to take advantage of the absorbing boundary conditions (the cell 512th in Figure 8).…”
Section: Methodsmentioning
confidence: 99%